2021
DOI: 10.1002/admt.202100885
|View full text |Cite
|
Sign up to set email alerts
|

Sonoporation: Past, Present, and Future

Abstract: only contribute to fundamental studies in areas of biology, bioengineering, and medicine, but also benefit several life-changing technologies, such as cell-based therapies, protein therapeutics, vaccines, as well as the reprogramming of cells. [22] Among the current delivery approaches, the viral vector-based approach is often considered the gold standard for the delivery of nucleic acids. [22] However, due to notable weaknesses such as biohazards, inconsistent results, and labor-intensive manufacturing, [22][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 237 publications
(293 reference statements)
0
20
0
Order By: Relevance
“…As shown in (Figures 2(a) and 2(b)), it can be clearly seen that the uptake of RPL NPs in the presence of LIFU was significantly enhanced in LIFU-treated RPL NPs compared to that in free RB, no-LIFU case. The results showed that the cavitation effects [ 32 ] and sonoporation [ 33 ] due to the LIFU-triggered UTMD could lead to higher uptake of RPL NPs. In conclusion, these data demonstrated that the prepared NPs can be taken up by many cells and suggested that the LIFU-triggered UTMD effect can further enhance the total drug uptake.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in (Figures 2(a) and 2(b)), it can be clearly seen that the uptake of RPL NPs in the presence of LIFU was significantly enhanced in LIFU-treated RPL NPs compared to that in free RB, no-LIFU case. The results showed that the cavitation effects [ 32 ] and sonoporation [ 33 ] due to the LIFU-triggered UTMD could lead to higher uptake of RPL NPs. In conclusion, these data demonstrated that the prepared NPs can be taken up by many cells and suggested that the LIFU-triggered UTMD effect can further enhance the total drug uptake.…”
Section: Resultsmentioning
confidence: 99%
“…The irradiation of bacteria with ultrasound both in the absence ( Figure 3 (b2)) and in the presence ( Figure 3 (b4–b6) of m-PSi NPs at the concentration of 1 g/L leads to the deformation of bacterial cells, but its behavior differs for the two cases. While separate ultrasound treatment leads to the “roughness” of bacterial surface attributed to the mechanical disturbance of the membrane, m-PSi NPs initiate cavitation effects such as cumulative jets [ 64 ], which result in sonoporation [ 65 ] clearly visible by hollows across the surface. Considering a low possibility of random influence of jets from bubbles far away from the bacteria, we could suppose that the interaction of m-PSi NPs with bacteria promotes the cavitation phenomena in the vicinity of the bacterial surface.…”
Section: Resultsmentioning
confidence: 99%
“…These are known to enhance transient poration of cell membranes and are being explored for their in vitro and in vivo uses, and for their potential clinical applications in gene therapy and drug delivery ( Carugo et al, 2011 ). However, at high pressure CAs can collapse and have the potential to cause capillary rupture and endothelial cell damage in vivo and cell rupture ex vivo and may reduce the effectiveness of delivered cargoes ( Rich et al, 2022 ). Carugo et al (2011) demonstrated acoustoporation of cardiac myoblasts in the absence of CAs using a cost-effective ultrasound-microfluidic device, which allowed for control over the position of the cells and the strength of the acoustofluidic forces.…”
Section: Physical and Energetic Methods Of Deliverymentioning
confidence: 99%